2008
DOI: 10.1159/000135606
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Altering Airway Smooth Muscle Cell Ca<sup>2+</sup> Homeostasis in Two Asthma Models

Abstract: Background: Asthma is characterized by airway remodeling, altered mucus production and airway smooth muscle cell (ASMC) contraction causing extensive airway narrowing. In particular, alterations of ASMC contractility seem to be of crucial importance. The elevation of the cytoplasmic Ca2+ concentration is a key event leading to ASMC contraction and changes in the agonist-induced Ca2+ increase in ASMC have been reported in asthma. Objective: The aim of this study was to investigate mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Recently, many studies have suggested the important role of intracellular Ca 2 + , indicating that an increase of cytosolic Ca 2 + concentration in bronchial smooth muscle cells might cause bronchial obstruction and bronchospam (Parekh and Penner, 1997;Sweeney et al, 2002). In the airway smooth muscle cells, the altered Ca 2 + homeostasis of the SR has also been shown to affect airway remodeling, including changes in expressions of immune-related molecules (Kellner et al, 2008). Furthermore, the correlation between SR Ca 2 + regulation and proinflammatory cytokines has been reported in human airway smooth muscle (Sathish et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many studies have suggested the important role of intracellular Ca 2 + , indicating that an increase of cytosolic Ca 2 + concentration in bronchial smooth muscle cells might cause bronchial obstruction and bronchospam (Parekh and Penner, 1997;Sweeney et al, 2002). In the airway smooth muscle cells, the altered Ca 2 + homeostasis of the SR has also been shown to affect airway remodeling, including changes in expressions of immune-related molecules (Kellner et al, 2008). Furthermore, the correlation between SR Ca 2 + regulation and proinflammatory cytokines has been reported in human airway smooth muscle (Sathish et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the elevated concentration of cytoplasmic Ca 2 + is a crucial event leading to the contraction of airway smooth muscle cells that causes extensive airway narrowing (Cox et al, 2007;Kellner et al, 2008). The SR is a complex internal membrane system that releases and reuptakes Ca 2 + during muscle contraction and relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, Nippostrongylus brasilienses infection up-regulates the expression of 5-HT 2A receptors in non-vascular smooth muscle and this effect is ascribed to IL-13 (Zhao et al 2006). Concerning intracellular receptors, IL-4 and IL-13, cytokines involved in the pathophysiology of asthma and schistosomiasis, upregulate the expression of ryanodine receptors in airway smooth muscle cells (Jude et al 2008, Kellner et al 2008. Therefore, these vascular alterations involving 5-HT 2A receptors and their signalling pathways could implicate 5-HT both in portal hypertension (Bosch et al 1992, Kaumann & Levy 2006 and secondary extra-portal vascular alterations occasionally observed in schistosomiasis as, for example, pulmonary hypertension (de Cleva et al 2003, Franco-Paredes et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…During an asthma attack, the tracheal smooth muscle plays an important role in reducing pulmonary function as it contracts [1][2][3][4]. Singulair (Montelukast) is commonly used to solve this problem.…”
Section: Introductionmentioning
confidence: 99%